Trans-generational family relations : investigating ambivalences - Albert, Isabelle; Abbey, Emily; Valsiner, Jaan (Perspectives on human development., 2018)
"The present volume deals with the experience of ambivalence in family relations - a well-known phenomenon that has inspired more and more research and theorizing in the last years but that is however sometimes difficult to capture. Bringing together junior and senior researchers from different parts of the world, ideas on theory and research are elaborated following qualitative and quantitative approaches. This book thus contributes to theory-building as well as outlining research results and helping to develop measurement in interpersonal and intergenerational relations"--